LITERATURE REVIEW : THE INFLUENCE OF JOB INSECURITY, JOB INVOLVEMENT, AND JOB SATISFACTION ON GOJEK DRIVER TURNOVER INTENTION IN BEKASI CITY - Lufiana Anggrainie (Draf Solusi Indonesia, 2023)
This research is a literature review that examines theinfluence of job insecurity, job involvement and jobsatisfaction on turnover intention. This researchfocuses on online motorcycle taxi drivers in BekasiCity. The population in this study is not known withcertainty but the approach used for the minimumsample was adopted from Lemeslow with a total of100 respondents.SPSS statistical tools are used to test the feasibility ofresearch data, namely validity and reliability and testclassic assumptions (normality, heteroscedasticity,multicollinearity and multiple linear regression andanswer research hypotheses with t and f tests anddetermination.